Tidal power proceedings of the symposium organized by the Institution of Civil Engineers and held in London, 30-31 October 1986. (Thomas Telford, 1987)
Following on from an opening address by D. Hunt, these papers provide an introduction to the work of the Severn Tidal Power Group. They focus on power generation studies of a barrage on the Severn, and implementation, organisation and project planning.
Keywords: Tidal power -- Great Britain -- Congresses.; Barrages -- England -- Mersey River -- Congresses.; elektronické knihy; electronic books